Cellular Bioenergetics: Role of Coupled Creatine Kinases 1994
DOI: 10.1007/978-1-4615-2612-4_13
|View full text |Cite
|
Sign up to set email alerts
|

Creatine kinase in non-muscle tissues and cells

Abstract: Over the past years, a concept for creatine kinase function, the 'PCr-circuit' model, has evolved. Based on this concept, multiple functions for the CK/PCr-system have been proposed, such as an energy buffering function, regulatory functions, as well as an energy transport function, mostly based on studies with muscle. While the temporal energy buffering and metabolic regulatory roles of CK are widely accepted, the spatial buffering or energy transport function, that is, the shuttling of PCr and Cr between sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
137
0
6

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(144 citation statements)
references
References 203 publications
1
137
0
6
Order By: Relevance
“…34 ± 36 Creatine may decrease the e ects of trauma-induced hypoxia especially by bu ering intracellular ATP. 15,37 Due to improved cellular energetics, the cells are likely to be more resistant against calcium overload and noxious acidic pH values. 37 Additionally, neurons can be protected by creatine by inhibition of mitochondrial permeability transition pore opening via the stabilizing action of mitochondrial CK octamers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 ± 36 Creatine may decrease the e ects of trauma-induced hypoxia especially by bu ering intracellular ATP. 15,37 Due to improved cellular energetics, the cells are likely to be more resistant against calcium overload and noxious acidic pH values. 37 Additionally, neurons can be protected by creatine by inhibition of mitochondrial permeability transition pore opening via the stabilizing action of mitochondrial CK octamers.…”
Section: Discussionmentioning
confidence: 99%
“…15,37 Due to improved cellular energetics, the cells are likely to be more resistant against calcium overload and noxious acidic pH values. 37 Additionally, neurons can be protected by creatine by inhibition of mitochondrial permeability transition pore opening via the stabilizing action of mitochondrial CK octamers. 38 Furthermore, creatine's neuroprotective activity may also be related to its inÂŻuence on the synthesis and release of neurotransmitters.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of increased carbonyl levels and decreased activity of CK further determines which crucial enzymes are finely involved in energetic impairments in this disorder. The CK system, consisting of a cytosolic and a mitochondrial isoform (MtCK) together with their substrates creatine and phosphocreatine, is one of the most important immediate energy buffering and transport systems of the cell, especially in muscle and neuronal tissue (394). CKs are prime targets of oxidative damage (74), leading to inactivation of both isoforms.…”
Section: Redox Proteomics-transgenic Mouse Model Of Hdmentioning
confidence: 99%
“…Accordingly, in vivo studies have suggested a direct coupling of CKATPase (2). An increase in CKB activity and brain energy metabolism constitutes a mechanism for coupling energy production (ATP) and energy storage (creatine phosphate) to meet rapidly increasing cellular energy demands (35). Muscle-type CK is functionally coupled to Na Ï© -K Ï© -ATPase activity, providing ATP for the ATPase reaction (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Three cytosolic CK isozymes [BB-CK (brain), MM-CK (muscle), and MB-CK (heart, lungs, stomach) (5, 8)] and two mitochondrial forms [sarcomeric MiCK (expressed mainly in heart and skeletal muscle and probably in some brain cells such as Purkinje neurons) and ubiquitous MiCK (expressed in many tissues)] are kinetically very similar but differ in their capacity to associate with subcellular organelles or protein structures (35,41). Three types (brain, muscle, and mitochondria) of CK have been demonstrated to exist in teleosts (4,26).…”
mentioning
confidence: 99%